Determinants Influencing Financial Performance of Listed Firms: Quantile Regression Approach - Hoang, Thi Viet Ha; Dang, Ngoc Hung; Tran, Manh Dung; Vu, Thi Thuy Van; Pham, Quang Trung (Asian Economic and Financial Review, 2019)
This research is conducted to assess the factors influencing financial performance of listed firms on Vietnam Stock Exchange. The factors include capital structure, firm size, short-term liquidity, fixed asset investment, growth rate and receivable management. Data were collected from audited financial statements of 269 large listed firms for the period from 2010 to 2016. Quantile regression and Ordinary Least Square regression (OLS) have been used for processing the multi-year dataset. The results show that firm size has a positive relationship with financial performance. In contrast, capital structure, short-term liquidity and fixed asset investment have negative relationship with financial performance. Meanwhile growth rate and receivable management has no impact on financial performance at the low level but different effects at different quantiles. In case of measuring ROS, ROA and ROE as proxies of financial performance, the results are heterogeneous.